Associations of overweight/obesity with patient-reported outcome measures after oblique lumbar interbody fusion - Hsueh, Lan-Li; Wu, Yun-Che; Pan, Chien-Chou; Shih, Cheng-Min; Lee, Cheng-Hung; Wang, Jun-Sing; Chen, Kun-Hui (Frontiers in Surgery, 2024)
Background: Oblique lateral interbody fusion (OLIF) combined with transpedicular screw fixation has been practiced for degenerative spinal diseases of elderly patients for years. However, overweight patients have been shown to have longer operative times and more complications from surgery. The effect on clinical outcome is still uncertified. The objective of this study was to determine is overweight a risk factor to clinical outcome of OLIF combined with transpedicular screw fixation technique. Material and methods: A retrospective study in patients submitted to OLIF combined with transpedicular screw fixation from January 2018 to August 2019 was conducted. VAS score, ODI score and EQ5D were measured before the operation and one year after the operation. Results: A total of 111 patients were included with 48 patients in the non-obese group and 55 patients in the overweight/obese group. There was no significant difference between the two groups in gender, age, smoking history, hypertension, chronic kidney disease and diabetes mellitus. Overweight/obese group has higher BMI (28.4 v.s. 22.7, p<0.001) than non-obese group. There was no difference between the two groups in pre-operative VAS score, ODI score and EQ5D score. However, the healthy weight group improved much more than the overweight score in VAS score, ODI score and EQ5D score. Conclusion: The overweight/obese patient group had clinical outcomes worse than the non-obese group in terms of pain relief and life functions.